Is there any association between psoriasis, psoriatic arthritis and thyroid autoimmunity?. (18th October 2020) - Vastarella, Maria; Megna, Matteo; Lupoli, Gelsy Arianna; Napolitano, Maddalena; Gallo, Lucia; Balato, Anna; Tasso, Marco; Costa, Luisa; Fabbrocini, Gabriella; Peluso, Rosario
Abstract: Background: Autoimmune diseases share a significant part of their genetic background and tend to coexist in the same patient. Some studies have investigated the possible association between autoimmune thyroiditis and psoriasis or psoriatic arthritis (PsA), with conflicting results. This study aimed to investigate the prevalence of autoimmune thyroiditis in psoriatic patients with (PsA) or without (PsC) joint involvement. Methods: 208 patients with psoriasis and/or PsA were recruited. These patients were divided into two groups: psoriasis patients (without PsA) (PsC group: 100 patients; mean age of 50.1 ± 11.7 years) and subjects with psoriasis and psoriatic arthritis (PsA group: 108 subjects: mean age of 39.8 ± 10.8 years). Assessment of psoriasis severity was conducted using the Psoriasis Area and Severity Index (PASI) score. The diagnosis of psoriatic arthritis was made according to CASPAR criteria. All patients had thyroid evaluation through evaluation of thyroid function, thyroperoxidase antibodies and thyroid ultrasound examination. Results: A statistically significant difference was found between the prevalence of autoimmune thyroiditis in the PsA group than the PsC group (25.9 vs 9.0 %; P = 0.018) with higher trends to hypothyroidism in the PsA group compared to the PsC group (13.9% vs 2.0%, P = 0.0018). Conclusions: The higher prevalence of autoimmune thyroiditis in the PsA group may be due to an immune dysfunction pathway in patients with psoriatic arthritis with a higher risk to develop other autoimmune diseases. This evidence confirms that psoriatic arthritis is an autoimmune disease with an overactive immune system that can involve multiple organs. Thyroid function evaluation should be part of the clinical and laboratory examination of patients with psoriatic arthritis.